Antioxidant and antimicrobial properties of propolis from different geographic regions in UAE and its applications in shelf-life extension of beef burger - Al Marzooqi, Hassan Mohamed; Shehata, Mohamed Gamal; Afifi, Hanan Sobhy; Masry, Saad H. D.; Aslam, Raouf; Srikumar, Shabarinath; Maqsood, Sajid (Frontiers in Sustainable Food Systems, 2025)
Based on their geographical origins, the functional compound profile of beehive propolis varies significantly. The present study evaluates the phenolic and flavonoid, antioxidant, and antimicrobial activities of propolis extracts (PE) sourced from four different geographical areas in the UAE. The Kuwaitat and Al-Wathba propolis extracts were further used as an additive in minced beef burger to demonstrate their natural preservative effects to enhance shelf life and keeping quality over 15 days of refrigerated storage. Kuwaitat and Al-Wathba propolis ethanol extracts using DPPH assays with IC50 0.30 ± 0.052 and 0.28 ± 0.002 mg/mL, respectively, showed highest antioxidant activities. The HPLC analysis of phenolic profile in Kuwaitat and Al-Wathba propolis extracts confirmed the presence of polyphenolic compounds including vanillic acid, p-coumaric acid, resveratrol, and quercetin. Furthermore, Al-Wathba and Kuwaitat sourced propolis exhibited good antimicrobial activity against various pathogenic strains. The total aerobic counts in meat burger products incorporated with Kuwaitat and Al-Wathba propolis extracts were 25 and 25.6% lower than the untreated meat products, respectively, with the Al-Wathba extract fortified burger exhibiting a shelf life of 9 days in chilled storage which was 67% higher than the untreated samples. These fortified meat burger formulations also showed significant inhibition rates against Escherichia coli and Salmonella senftenberg after 15 days of refrigerated storage, respectively. These findings suggest that beehive propolis from four different UAE regions have good antioxidant and antimicrobial properties and can be safely used to improve shelf-life safety in minced beef products.